2010
DOI: 10.1007/s11259-010-9364-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in pigs induced by recombinant canine adenovirus 2 expressing the glycoprotein 5 of porcine reproductive and respiratory syndrome virus

Abstract: To develop a new type vaccine for porcine reproductive and respiratory syndrome (PRRS) prevention by using canine adenovirus 2(CAV-2) as vector, the Glycoprotein 5(GP5) gene from PRRSV strain JL was amplified by RT-PCR, and the expression cassette of GP5 was constructed using the human cytomegalovirus (HCMV) promoter and the simian virus 40 (SV40) early mRNA polyadenylation signal. The expression cassette of Glycoprotein 5 was cloned into the CAV-2 genome in which E3 region had been partly deleted, and the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…More recently, two independent reports have concluded that the GP5 ectodomain does not contain a linear neutralizing epitope in PRRSV type 1 (Vanhee et al, 2011) or in PRRSV type 2 (Li and Murtaugh, 2012) strains. In summary, the original observation that DNA immunization with the single GP5 gene alone can evoke antibodies that efficiently neutralize PRRSV infectivity still holds true and has been confirmed by multiple subsequent independent reports that used GP5 as possible subunit candidate to make experimental vaccines (based on GP5 alone or in GP5/M expressed as a dimer) (Jiang et al, 2007;Kim et al, 2013;Pirzadeh and Dea, 1998;Vanhee et al, 2011;Xu et al, 2012;Zheng et al, 2007;Zhou et al, 2010). In all these cases GP5 alone or GP5/M expressed in multiple different vaccine platforms have elicited PRRSV-neutralizing antibodies.…”
Section: Where On the Prrsv Virion Are Neutralizing Epitopes Located?mentioning
confidence: 83%
“…More recently, two independent reports have concluded that the GP5 ectodomain does not contain a linear neutralizing epitope in PRRSV type 1 (Vanhee et al, 2011) or in PRRSV type 2 (Li and Murtaugh, 2012) strains. In summary, the original observation that DNA immunization with the single GP5 gene alone can evoke antibodies that efficiently neutralize PRRSV infectivity still holds true and has been confirmed by multiple subsequent independent reports that used GP5 as possible subunit candidate to make experimental vaccines (based on GP5 alone or in GP5/M expressed as a dimer) (Jiang et al, 2007;Kim et al, 2013;Pirzadeh and Dea, 1998;Vanhee et al, 2011;Xu et al, 2012;Zheng et al, 2007;Zhou et al, 2010). In all these cases GP5 alone or GP5/M expressed in multiple different vaccine platforms have elicited PRRSV-neutralizing antibodies.…”
Section: Where On the Prrsv Virion Are Neutralizing Epitopes Located?mentioning
confidence: 83%
“…These efforts reportedly included use of several adjuvants [40][41][42] , use of mixed strains of PRRSV [43,44] , and generation of alternative vaccines, i.e. DNA vaccine [45,46] , subunit vaccine [47,48] , synthetic peptide vaccine [13] , viral vector vaccines using adenovirus [49][50][51] , PRV [52,53] , poxvirus [54,55] , and transmissible gastroenteritis virus [56] as vectors, alphavirusderived replicon [57] , bacterial vector vaccine [58] , insect cellderived vaccine [59] , and plant-derived vaccine [60,61] (Table 4). These efforts, however, can achieve at best some, but not all, properties of an ideal PRRS vaccine.…”
Section: Current Efforts On Prrs Vaccine Developmentmentioning
confidence: 99%
“…However, PRRSV MLV vaccines have myriad concerns with respect to efficacy and safety, such as ineffective protection against heterologous strains, reversion of vaccine to pathogenic virus and shedding of infective virus upon vaccination. Several experimental vaccines have been reported, including mixed strain vaccines [ 22 , 23 ], recombinant subunit vaccines bearing different PRRSV structural proteins, such as DNA [ 24 , 25 ], bacteria [ 26 ], adenovirus [ 27 , 28 , 29 ], poxvirus [ 30 , 31 ], alphavirus [ 32 ], baculovirus [ 33 ] and gastroenteritis virus [ 34 ], plant-derived vaccines [ 35 , 36 , 37 ] and synthetic peptide vaccines [ 38 ]. These vaccines can confer protection at its best, but do not possess the characteristics of a universal PRRS vaccine.…”
Section: Discussionmentioning
confidence: 99%